Correlation of Body Consciousness and Fear of Negative Appearance With Self-Esteem in University Students - Shahid, Noman; Sarwar, Amna; Qubtia, Maria; Umar, M.; Hassan, Ahmad; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2024)
Objective: The purpose of this study was to evaluate the correlation between body image consciousness and fear of negative social appearance with self-esteem and confidence, and try to understand the attitudes regarding body image and the factors that lead to fear of negative appearance and low self-esteem. Study design: A cross-sectional study.Place and Duration of Study: The study was conducted online and the link to the questionnaire was shared through several social media platforms such as Facebook and WhatsApp. The study was conducted from Apr 2021 to Aug 2021.Methodology: A cross-sectional study was done through an online survey that was created using google form. It used the Objectified Body Consciousness Scale (McKinley & Hyde, 1996), Fear of Negative Appearance evaluation scale (Lundgren,Anderson, & Thompson,2004), The Rosenberg Self-Esteem Scale (Rosenberg, 1965).Result: A total of 561 responses were received in which 66.2% were female and 33.1% were males. Those responses were analyzed through SPSS2. The results demonstrated a direct proportionality between body image consciousness and a fear of negative social appearance while they demonstrated an inverse proportionality with self-esteem and confidence. It also showed that females have greater tendency for body surveillance, body shaming, fear, anxiety and low self-esteem related to it as compared to males. The Pearson correlation indicated a significant positive correlation between low self-esteem and family financial status.Conclusions: Body image consciousness and its related fears are found in both male and female university students. Social appearance has psychological effects on students. The low self-esteem is related to negative body appearance. Financial statusalso affects self-esteem related to body image or to the fear of negative appearance. Females are more conscious about body image than males.